Correlation of Total Thyroid Volume with Thyroid Hormone among Pregnant and Non Pregnant Women in Local Population, karachi - Hira Ahmed, Soofia Nigar, Shazia Fahmi, Hina Jabeen, Raffat Rasool, Mahrukh Kamran (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The goal of the study was to find a link between the total size of the thyroid as measured by ultrasonography and the levels of thyroid hormones (TSH and FT4) in pregnant and non-pregnant women in Karachi. Methodology: Between October 2016 and December 2018, the DUHS Ojha Campus in Karachi, Pakistan, hosted a clinical study in the Gynecology Outpatient Department (OPD) and the Radiology Department. Two groups of women between the ages of 14 and 45 who could bear children and were therefore candidates for recruitment (pregnant and non-pregnant women). Using an ultrasound, the total volume of the thyroid was accurately measured after ensuring that certain inclusion and exclusion criteria had been met. Thyroid hormone levels were measured using blood drawn from each of the women (TSH and FT4). At the Ojha campus of the Dow University of Health Sciences, the Ojha Diagnostic Research and Reference Laboratory, the blood test was performed (DDRRL). Results: The study had 100 participants, 50 of whom were pregnant and the other 50 who were not. Total thyroid volume and the results of blood tests like serum TSH and FT4 were taken into account when comparing the two groups. Thyroid hormone levels were inversely correlated with thyroid volume in both groups of participants. Pregnant women had a total thyroid volume of 7.023.21, compared to 5.582.41 in non-pregnant women. When the p-value was less than 0.001, it was clear that the number of women who were pregnant had increased significantly. A pregnant woman’s TSH level was 1.801.11 IU/mL, which was significantly higher than that of a non-pregnant woman’s TSH level (p-value = 0.01). Non-pregnant women had an average FT4 level of 1.230.44 ng/dL, while pregnant women had an average FT4 level of 0.960.13 ng/dL. Conclusion: So, our study shows that at least half of the pregnant women in our population do have some kind of thyroid hormone deficiency. During pregnancy, the size of the gland grows, which is a sign of an iodine deficiency.